Genomic and immune profiling of pre-invasive lung adenocarcinoma - Haiquan Chen (Nature Portfolio, 2019)
The genomic and immune landscape of pre-invasive lung adenocarcinoma is poorly understood. Here, the authors perform exome and transcriptome sequencing on precursor legions and invasive lung adenocarcinomas, identifying recurrently mutated genes in pre/minimally invasive cases, and arm level alteration events linked to immune infiltration.